SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI KARYAWAN KONTRAK DI RS MITRA JAMBI MENGGUNAKAN METODE WASPAS: DECISION SUPPORT SYSTEM FOR CONTRACT EMPLOYEE SELECTION AT RS MITRA JAMBI USING THE WASPAS METHOD - Muhammad Hendrik Koto; Dodo Zaenal Abidin; Sharipuddin (LPPM Universitas Abdurrab, 2025)
This research aims to develop a decision support system (DSS) to improve the efficiency and objectivity of contract employee selection at Mitra Jambi Hospital. The main problem faced by RS Mitra Jambi is the absence of a special information system for the selection of contract employees, which causes the assessment process to be manual, slow down the workflow, and tend to be subjective. This system is designed using the Weighted Aggregated Sum Product Assessment (WASPAS) method which is proven to be able to produce measurable, transparent, and accurate assessments, by integrating various assessment criteria such as Education, Competence, Motivation, and Attitude to rank candidates. The system development process follows the waterfall method, including requirements analysis, design, implementation, and black-box testing. This web-based system is built with PHP and MySQL database. The results of implementation and testing show that all system functionality runs well, is able to provide more accurate recommendations, reduce subjectivity, and increase selection effectiveness. However, this study has limitations in data validation, namely the use of 1 real data and 29 simulated data from 30 candidates, due to the absence of comprehensive historical data recapitulation at Mitra Jambi Hospital. This system is expected to optimize the quality of selected candidates and support HR management at RS Mitra Jambi in a professional and accountable manner.